The BTB-kelch protein KLEIP controls endothelial migration and sprouting angiogenesis - Nacak, Tanju; Alajati, Abdullah; Leptien, Kerstin; Fulda, Christine; Weber, Holger; Miki, Toru; Czepluch, Frauke S.; Waltenberger, Johannes; Wieland, Thomas; Augustin, Hellmut; Kroll, Jens (Circulation research, 2007)
Sprouting and invasive migration of endothelial cells are important steps of the angiogenic cascade. Vascular endothelial growth factor (VEGF) induces angiogenesis by activating intracellular signal transduction cascades, which regulate endothelial cell morphology and function. BTB-kelch proteins are intracellular proteins that control cellular architecture and cellular functions. The BTB-kelch protein KLEIP has been characterized as an actin-binding protein that interacts with the nucleotide exchange factor ECT2. We report that KLEIP is preferentially expressed in endothelial cells, suggesting that it may play a critical role in controlling the functions of migrating, proliferating, and invading endothelial cells during angiogenesis. KLEIP mRNA level in endothelial cells is strongly regulated by hypoxia which is controlled by hypoxia-inducible factor-1α. Functional analysis of KLEIP in endothelial cells revealed that it acts as an essential downstream regulator of VEGF- and basic fibroblast growth factor-induced migration and in-gel sprouting angiogenesis. Yet, it is not involved in controlling VEGF- or basic fibroblast growth factor-mediated proliferative responses. The depletion of KLEIP in endothelial cells blunted the VEGF-induced activation of the monomeric GTPase RhoA but did not alter the VEGF-stimulated activation of extracellular signal-regulated kinase 1/2. Moreover, VEGF induced a physical association of KLEIP with the guanine nucleotide-exchange factor ECT2, the depletion of which also blunted VEGF-induced sprouting. We conclude that the BTB-kelch protein KLEIP is a novel regulator of endothelial function during angiogenesis that controls the VEGF-induced activation of Rho GTPases.